Triple pelvic osteotomy as treatment for osteoarthritis secondary to developmental dysplasia of the hip - Janssen, Dirk (Springer-Verlag, 2009)
Joint-preserving osteotomies are an established treatment for adult hip pain secondary to developmental dysplasia of the hip. However, their value for advanced osteoarthritis is unclear. Therefore this study addresses the question of long-term results of triple pelvic osteotomy in patients with second grade osteoarthritis. Thirty-two patients with second grade osteoarthritis secondary to developmental dysplasia of the hip before triple pelvic osteotomy were clinically and radiographically assessed 11.5 years postoperatively. Five patients required conversion to total hip replacement. Kaplan-Meier survivorship analysis predicted a survival rate of 85.3%. The mean Harris hip score increased significantly with more than 56% good or very good results. A preoperative BMI > 25 and Harris hip score < 70 resulted in worse outcome or early conversion into total hip arthroplasty. The results indicate that developmental dysplasia of the hip even in second grade osteoarthritis can be treated with triple pelvic osteotomy.